1992
DOI: 10.1108/07363769210037033
|View full text |Cite
|
Sign up to set email alerts
|

Celebrity Endorsers: Do You Get What You Pay For?

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 1 publication
1
36
0
2
Order By: Relevance
“…Brand extensions, which deviate from their identity, are looked upon skeptically by consumers (Smith and Adrews, 1995). Also, this fit may be designated as similarity, congruity, fittingness, match-up, and consistency in the context of other brand alliances and brand extensions (Tauber, 1981;Kamins 1990;Solomon et al, 1992;Walker et al, 1992;Lynch and Schuler, 1994;Simonin and Ruth, 1998;Till and Busler, 2000). However, concepts such as similarity and fit cannot adequately explain a consumer's cognitive evaluation of comarketing alliances that involve two different industries.…”
Section: Brand Extensionmentioning
confidence: 97%
“…Brand extensions, which deviate from their identity, are looked upon skeptically by consumers (Smith and Adrews, 1995). Also, this fit may be designated as similarity, congruity, fittingness, match-up, and consistency in the context of other brand alliances and brand extensions (Tauber, 1981;Kamins 1990;Solomon et al, 1992;Walker et al, 1992;Lynch and Schuler, 1994;Simonin and Ruth, 1998;Till and Busler, 2000). However, concepts such as similarity and fit cannot adequately explain a consumer's cognitive evaluation of comarketing alliances that involve two different industries.…”
Section: Brand Extensionmentioning
confidence: 97%
“…In 1990, Misra and Beatty defined congruence as occurring when the relevant characteristics of the endorser are consistent with the relevant attributes of the brand. Consistency is also the term used by Walker, Langmeyer, and Langmeyer (1992). Kamins and Gupta (1994) use congruence, fit and match interchangeably, although they do not define any of them.…”
Section: Introductionmentioning
confidence: 97%
“…Mowen, Wiener, and Joag (1987) found that as perceived expertise of a source increases, its level of persuasion also increases. Similarly, Walker, Langmeyer, and Langmeyer (1992) found perceived expertiseamong a host of other source characteristics-to be the only factor to significantly influence the purchase intentions of consumers. The influence of expertise on behavior has also been documented (Busch & Wilson, 1976;Crisci & Kassinove, 1973;Liu & Leach, 2001;Taylor & Woodside, 1982;Woodside & Davenport, 1974;Woodside & Pitts, 1975).…”
Section: H3bmentioning
confidence: 95%